ANALISIS PERILAKU MASYARAKAT DALAM MENJAGA KEBERSIHAN LINGKUNGAN, LINGKUNGAN VI KELURAHAN CENGKEH TURI KECAMATAN BINJAI UTARA PROVINSI SUMATERA UTARA - Muhammad Angga Reksa; Julia Putri Zahara; Putri Faradilla; Widia Anggraini; Muhammad Syahbudi (PKM Maju UDA, 2021)
This research is motivated by the behavior of the community in maintaining environmental cleanliness, Environment VI, Cengkeh Turi Village, North Binjai District. Environment vi is one of six neighborhoods in Cengkeh Turi Village, North Binjai, North Sumatra Province. To find out the behavior of the community in maintaining environmental cleanliness, the researchers used a qualitative approach and conducted research with a number of informants as many as 15 residents and 1 Head of the Environment as key informants. Based on the results of the research that has been carried out, the following results are obtained: 1) Community behavior regarding environmental cleanliness, Environment vi Kelurahan Cengkeh Turi, North Binjai District, can not be fully said to be good, because there are still people who throw garbage carelessly so that it is scattered on the roadside Not only that, there are also people who own livestock who do not have awareness in taking care of their livestock so that dirt and leftover food are scattered around the house which disturbs the comfort of the surrounding community. 2) Community efforts in maintaining environmental cleanliness, the Environment vi Cengkeh Turi Village, North Binjai District by cleaning their respective homes and disposing of household waste in containers/disposal places that have been provided in their respective yards. However, there are still people who arbitrarily burn their household waste in the yard, which disturbs the comfort of the surrounding community. 3) The role of the Head of the Environment in maintaining the cleanliness of the environment by holding mutual clean-up social activities which are carried out once or twice a month in their respective homes and also the prayer room, besides that the head of the environment is also active in conducting outreach regarding the importance of keeping the environment clean and reprimanding people who do not follow the direction of protecting the environment properly. The results showed that people's behavior in maintaining environmental cleanliness can be said to be good, although not yet one hundred percent.